Pelatihan Peregangan dan Penerapan Teknologi Alat Pemintal Ergonomis pada Penenun Tradisional di Desa Boti: Stretching Training and Application of Ergonomic Spinner Technology in Traditional Weavers in Boti Village - Ndun, Helga Jillvera Nathalia; Berek, Noorce Christiani; Littik, Serli K. A.; Dodo, Dominirsep Ovidius; Tarigan, Ben Vasco (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Traditional weavers are prone to musculoskeletal complaints. Yarn spinning, one of the weaving stages, can increase the risk of these complaints due to the bent sitting position, long periods with the hands raised, and repetitive work. Lack of stretching and limited technology for yarn spinning are issues found among weavers at Boti Village. This community service aims to increase knowledge and ability to stretch and apply alternative spinning tools to help weavers in spinning. Activities included stretching-related education and demonstration and assistance in using the tool. The activity results showed an increase in the ability of all weavers to practice stretching (40% in the moderate category and 60% in the good category). A poster containing 14 movements was given to weavers as a reminder to stretch. Weavers have tested the spinning tool but still need further assistance and regular use to improve the spinning efficiency.